Muslim heritage in the golden age, the house of wisdom and the knowledge management in enhancing the competitiveness of public universities in Malaysia - Mohamed Mahmoud, Fatimetou Zahra; Mohamed Mahmoud, Ahmed; Ahmad Dahlan, Abdul Rahman (Research Publish Journals, 2015)
The rapid change in the market needs had represent a challenge and request more work and adaption from the educational organizations to this change by changing their plans, strategies and curriculums in order to be able to sustain and graduate students who have the skills and knowledge that make them able to compete in the whole world. Actually, this challenge was facing all the universities worldwide especially the Islamic universities which has a special and different vision and goals based not only on the scientific knowledge but in the holistic development of the students. For this, this empirical analysis was done to prove the efficiency of having the knowledge management as a tool in addition to the knowledge legacy from the Islamic golden age as a way to improve the Islamic universities performance. Also, how we can make link between the current universities and the old Islamic universities such as house of wisdom to extract lessons and learn from this successful pattern which was the main point of creativity, innovation and the place where most of the inventions which are the base of our modern world was invented in that university or academy. This research was based on empirical findings conducted from interviews with a number of professionals who had experience of work in Islamic universities and who came from different background and levels.